Stock price volatility and fundamental value: evidence from Central and Eastern European countries - Gajdka, Jerzy; Pietraszewski, Piotr (Economics and Business Review, 2017)
The paper deals with the problem of the discrepancy between fundamental values of shares in the stock market and their market prices. In particular it discusses the problem of the excessive volatility of stock prices compared with changes in their fundamental value determined as the present value of dividends paid by the company. The results of research on this issue for the US market initiated and popularized by Robert Shiller provided strong arguments against the hypothesis of capital market efficiency stating that stock prices immediately account for any new information affecting the fundamental value of assets. This problem has been studied neither for the Polish stock market nor for other post-communist countries in Central and Eastern Europe. The paper presents preliminary results of research into these stock markets. .